(untitled) (Canadian Hematology Today, 2025)
Novel, highly effective therapies for multiple myeloma are raising hopes, while also adding complexity to treatment decisions and care management. Recently, Canadian Hematology Today sat down with two Canadian experts and discussed what the availability of novel therapies means for patients, and how clinical leaders are coordinating care to improve access for patients in Northern Ontario.